Reception Analysis of the ‘Achieve Your Dreams with Us’ Campaign Among Second-Semester Students of Universitas 17 Agustus 1945 Surabaya - Djatmiko, Benedictus Raflin Algra Triyoga; Palupi, Merry Fridha Tri; Sadono, Teguh Priyo (Indonesian Journal Publisher, 2025)
Intense competition among private higher education institutions (PHEIs) requires them to implement effective promotional campaigns to attract prospective students. This study examines the reception of second-semester students at Universitas 17 Agustus 1945 (UNTAG) Surabaya regarding the aspirational promise in the